Peak fat oxidation rate during walking in sedentary overweight men and women - Bogdanis, G.C.; Vangelakoudi, A.; M Maridaki (Journal of Sports Science and Medicine, 2008)
The aim of this study was to determine the relative exercise intensity that elicits maximal fat oxidation during walking in inactive and overweight men and women and evaluate any possible sex differences. Forty six healthy, sedentary, overweight men (age: 36.3±1.3 years, body fat: 28.8 ± 0.8%, n = 28, mean ± SE) and women (age: 36.6±1.8 years, body fat: 37.1 ± 0.8%, n = 18) participated in the study. Fat oxidation was calculated from expired air analysis using indirect calorimetry during an incremental treadmill walking test. Peak fat oxidation rate (PFO) was higher in men compared to women (0.31 ± 0.02 vs. 0.20 ± 0.02 g.min-1; p < 0.001), but this difference disappeared when PFO was scaled per kg fat-free mass (4.36 ± 0.23 vs. 3.99 ± 0.37 mg.kg fat free mass -1.min-1). Also, the relative exercise intensity at which PFO occurred was similar for men and women and corresponded to 40.1 ± 1.8 and 39.5 ± 2.3% of maximal oxygen uptake (VO2max) and 60.0 ± 1.4 and 57.8 ± 1.4% of maximal heart rate, respectively. The walking speed corresponding to PFO was 5.5 ± 0.2 and 5.0 ± 0.1 km·h-1 for men and women, respectively. Regression analysis showed that sex, FFM and VO2max were significant predictors of PFO expressed in g.min-1 (adjusted R2 = 0.48, p = 0.01). However when PFO was scaled per kg FFM, only a small part of the variance was explained by VO2max (adjusted R2 = 0.12, p < 0.05). In conclusion, peak fat oxidation rate and the corresponding relative exercise intensity were similar in male and female overweight and sedentary individuals, but lower compared to those reported for leaner and/or physically active persons. Walking at a moderate speed (5.0-5.5 km·h-1) may be used as a convenient way to exercise at an intensity eliciting peak fat oxidation in overweight individuals. ©Journal of Sports Science and Medicine (2008).
Keywords: Calorimetry; Exercise intensity; Substrate utilisation